People, population, prosperity, and place - Rolston, Holmes, 1932-2025, author; United Nations Environment Programme, publisher (Colorado State University. Libraries, 1994)
Ethical evaluation of the UN strategy document from the United Nations Conference on Environment and Development (Rio Earth Summit). Population growth, human health, and people living sustainably on their landscapes are the concerns of Chapters 5, 6, and 7, which follow the analyses of poverty and escalating consumption in Chapters 3 and 4. This leads to formulating policy in Chapter 8, concluding the social and economic section of Agenda 21. The world is a complicated place, reflected in this agenda, one of the longest international documents ever negotiated; but at risk of oversimplification we can sketch the ethical issues by a look a chronological graph of world population and a pie chart of world consumption.
Keywords: consumption; poverty; population growth; sustainability; United Nations conference on environment and development; Agenda 21; UNCED